PENGARUH GAYA KEPEMIMPINAN, MOTIVASI KERJA, DAN KAPASITAS INDIVIDU TERHADAP PRODUKTIVITAS KEPALA SMA DI JAKARTA - Ruknan, Ruknan (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2016)
The objective of the research was direct effect of leadership style, work motivation and individual capacity to principal productivity ofÂ  high school in Jakarta. Data for this study was collected through by survey, involving a randomly selected samples of 60 principals by using questionaire. Path analysis technique used to analyse the data. The result of the research are follow: 1) the style leadership positive direct effect on principals productivity, 2) the work motivation positive direct effect on principals productivity, 2) the individual capacity positive direct effect on principals productivity, 3) the style leadership positive direct effect on individual capacity, 4) the work motivation positive direct effect on individual capacity, and 6) the style leadership not positive direct effect on individual capacity. The result suggest that style leadership, work motivation, and individual capacity are important determinants to principals productivity.